2022
DOI: 10.1371/journal.pone.0262439
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic ductal adenocarcinoma: Prognostic indicators of advanced disease

Abstract: Background/Objectives Pancreatic ductal adenocarcinoma (PDAC) is an aggressive malignancy associated with high metastatic risk. Prognosis remains poor even after resection. Previously our group identified biomarkers that improved diagnostic accuracy in PDAC beyond the established diagnostic tumour marker, CA19-9. Risk factors, symptoms and circulating biomarkers associated with a PDAC diagnosis may differ from those that alter disease progression and metastasis. This study aimed at assessing the risk factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
(48 reference statements)
0
7
1
Order By: Relevance
“…According to this, the potential beneficial role of metformin has been studied [43], but we did not obtain significant results for its effect on OS. Despite our results for AHT and DM, no significant difference was seen in AHT and DM rates across PDAC stages in the literature [41].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…According to this, the potential beneficial role of metformin has been studied [43], but we did not obtain significant results for its effect on OS. Despite our results for AHT and DM, no significant difference was seen in AHT and DM rates across PDAC stages in the literature [41].…”
Section: Discussioncontrasting
confidence: 99%
“…A metanalysis did not observe a statistically significant association between AHT and pancreatic cancer [40]. On the other hand, the association between DM and PDAC has been reported, the prevalence of PDAC is higher in adults with new-onset DM than in the general population [41], and patients with this comorbidity have higher mortality overall [42]. According to this, the potential beneficial role of metformin has been studied [43], but we did not obtain significant results for its effect on OS.…”
Section: Discussionmentioning
confidence: 92%
“…[ 43 ] In a study of 131 South African PDAC and benign control patients, IFN‐γ, IL‐4, IL‐5, IL‐15, and IL‐17 levels decreased in the PDAC group, whereas IL‐8, CXCL10 (IP‐10), and MIP‐1β levels increased, but the levels of IL‐2, IL‐6, IL‐7, IL‐9, IL‐10, IL‐12, IL‐13, IL‐21, IL‐22, and IL‐23 were similar in both groups. [ 44 ] Studies show that circulating inflammatory cytokine levels are still controversial in PDAC patients. In our study, we found that plasma IL‐5 and TNF‐α levels of the PDAC + LPS group decreased compared to the LPS group, whereas the IL‐10 level increased.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma is seldom detected at an early stage. The lag in detection is due to late clinical expression and the nonspecificity of symptoms like jaundice, abdominal pain, and oily stools 15,16 . This means patients are also considered for alternative diagnoses during medical needs, increasing the treatment response time needed.…”
Section: Late Diagnosismentioning
confidence: 99%
“…The lag in detection is due to late clinical expression and the nonspecificity of symptoms like jaundice, abdominal pain, and oily stools. 15,16 This means patients are also considered for alternative diagnoses during medical needs, increasing the treatment response time needed. Another reason for the late detection of PDAC is the lack of effective screening strategies and biomarkers to reliably detect early-stage PDAC or its precursor lesions.…”
Section: Late Diagnosismentioning
confidence: 99%